Процесс водородного восстановления трихлорсилана - Червоный, И. Ф.; Реков, Ю. В.; Головко, О. П. (НТУ "ХПИ", 2013)
Представлены результаты теоретического исследования о предварительном нагреве прутков-подложек в процессе водородного восстановления трихлорсилана– «Siemens-процесса». Обсуждаются применение легированных прутков-подложек для производства поликристаллического кремния с заданным уровнем концентрации легирующей примеси. В режиме генерации собственных носителей заряда, при нагревании кремния полупроводниковой чистоты в кристаллической решетке генерируются собственные носители заряда, которые обеспечивают определенную, в зависимости от температуры, электрическую проводимость. При использовании легированных прутков-подложек осуществляется расчет концентрации заданного типа примеси, с учетом величины нарощенного слоя поликристаллического кремния и перераспределения примеси между прутком-подложкой и объемом получаемых стержней поликристаллического кремния

Presented results of theoretical research about theprevious heating of slim-rods in the process of hydrogen renewal of trichlorosilane - "Siemens-process".. Applications of the alloyed slim-rods come into question for the production of polycrystallinesilicon with the set level of concentration of alloying admixture. Essence of "Siemens-process" consists inediting in the reactor of the silicon slim-rods, their warming-up to the temperature ~1500 Кand next hydrogen renewal of trichlorosilane on the surface of slim-rods. The warming-up of slim-rods is produced by a direct current. The size of electric resistance of slim-rods can be created by two variants - generation of own charge carriers or introduction to slim-rods of necessary amount of alloying element. In the mode of generation of own charge carriers, at heating of silicon of semiconductor cleanness own charge carriers which provide certain are generated in a crystalline grate, depending on a temperature,electric conductivity. At the use of the alloyed slim-rods the calculation of concentration of the set type of admixture is carried out, taking into accountthe size of the got layer of полікристалічногоsilicon and redistribution of admixture between slim-rods and by volume of the got bars of полікристалічногоsilicon
Keywords: кремний; прутки-подложки; носители заряда; легирование; примеси; нагрев; silicon; slim-rods; charge carriers; alloying; heating; admixtures